Integrating network pharmacology, molecular docking, and experimental verification to investigate the mechanism of baicalein in colorectal cancer - Wang, Jiahe; Han, Kunyu; Chen, Bingkun; Guo, Yupei; Zhao, Jinyan; Zhu, Xiaoqin; Lin, Jiumao; Chen, Yong (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Baicalein (BA) is a major bioactive flavonoid derived from Scutellaria baicalensis Georgi. Accumulating evidence has demonstrated that BA exhibits remarkable antitumor activity. However, the mechanisms underlying its effects in colorectal cancer (CRC) remain unclear. This study aimed to elucidate the potential therapeutic mechanisms of BA in CRC through an integrated approach using network pharmacology (NP), molecular docking, molecular dynamics simulations (MDS), and experimental validation.Methods: First, potential targets of BA and CRC were retrieved from public databases, and overlapping targets were identified. A protein-protein interaction (PPI) network was established, and candidate targets were analyzed using Gene Ontology (GO), Disease Ontology (DO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses to identify signaling pathways through which BA may exert therapeutic effects in CRC. The stability of ligand-receptor binding was evaluated via molecular docking and MDS. Finally, the identified core targets and associated signaling pathways were validated through in vitro assays.Results: NP analysis identified 171 overlapping targets between CRC and BA, with EGFR, AKT1, MAPK3 (ERK1), BCL2, GSK3B, and SRC identified as the core nodes. Molecular docking and MDS revealed that BA forms stable interactions with the kinase domain of EGFR. Integrated enrichment analysis and in vitro experiments demonstrated that BA exerted anti-CRC effects primarily through EGFR-mediated MAPK and PI3K/AKT signaling pathways.Conclusions: BA inhibits CRC progression by inhibiting EGFR activation and modulating MAPK and PI3K/AKT signaling pathways. These findings provide a theoretical basis for developing BA as a natural therapeutic agent for CRC treatment.